Impact of organizational innovation on product and process innovation. Issue 5 (4th July 2017) - Cozzarin, Brian Paul
ABSTRACT: The purpose of this paper was to test the effect of organizational innovation on product and process innovation (while controlling for endogeneity). Our hypothesis was that organizational innovation should have a significant and positive impact on technical (product or process) innovation. We control for endogeneity by using a Poisson estimator that accommodates a binary endogenous regressor. We test 10 potential instruments using a battery of test criteria and settle on five. All results are presented using the five instruments to avoid expectation bias. In general we find that organizational innovation does impact technical innovation positively. With the 2009 data we find that the mean of the average treatment effect for product innovation is roughly 1.7 times that of process innovation. For the 2009–2012 data we find that the impact on product innovation is roughly 1.5 times that of process innovation. For the 2012 data, we had anomalous results for process innovation, such that organizational innovation reduced the number of process innovations by 2.3 per year. In terms of Canadian government policy, the results lend support to the view that technical innovation is not the only innovation that matters. The right policy mix may encourage firms to experiment with and adopt more organizational innovations to enhance technical innovation.